Does birth under-registration reduce childhood immunization? Evidence from the Dominican Republic - Steve Brito; Ana Corbacho; Rene Osorio (Health Economics Review, 2017)
The consequences of lacking birth certificates remain largely unexplored in the economic literature. We intend to fill this knowledge gap studying the effect of lacking birth certificates on immunization of children in the Dominican Republic. This is an interesting country because a significant number of children of Haitian descent face the consequences of lacking proper documentation. We use the distance to the civil registry office and the mother's document of identification as instrumental variables of the child's birth certificate. After controlling for distance to immunization services and other determinants, this paper finds that children between 0 and 59 months of age that do not have birth certificates are behind by nearly one vaccine (out of a total of nine) compared to those that have birth certificates.
Keywords: 330; Immunization; Under-registration; Health access